Implementing modular mesearch consents using IHE advanced patient privacy consents - Schreiweis, Björn; Bronsch, Tobias; Merzweiler, Angela; Bergh, Björn (Building continents of knowledge in oceans of data, 2018)
The reuse of healthcare information for biomedical research is increasing and with it the importance of a consent management framework implementing computable consents. Based on requirements concerning a consent representation the Advanced Patient Privacy Consents (APPC) Profile of Integrating the Healthcare Enterprise (IHE) is evaluated and mapped to these requirements. As IHE APPC was developed for computable patient consents, the mapping of consents for research projects is possible by re-using the elements defined. Compared to other approaches like gICS, approaches using APPC can be based on commercial software products and integrated into IHE environments. IHE APPC was already successfully used in EHR projects like INFOPAT. For interoperability reasons IT platforms intending to support biomedical research including clinical data, research data, biomaterial and imaging data, IHE APPC seems to be an appropriate standard to choose.
Gesehen am 27.04.2020